Complications and patient satisfaction with urethral clean intermittent catheterization in spina bifida patients: comparing coated vs uncoated catheters. Issue 6 (December 2019) - Burki, Tariq; Abasher, Abdelazim; Alshahrani, Ahlam; Al Hams, Abdul Wahab; Ibrahim, Hanan; Albadawe, Hani; Al Modhen, Fayez; Jamalalail, Yasser; Al Shammari, Ahmed
Summary: Introduction: Many types of catheters are available in market for clean intermittent catheterization (CIC). Each company claim superiority of their products, but strong evidence is lacking. Purpose: To assess the complications due to CIC in spina bifida children and its possible relationship to hydrophilic-coated catheter (HCC) or uncoated catheters (UCCs), with a view to decrease catheter related complications, and improve patients experience and compliance. Materials and methods: The authors retrospectively reviewed the spina bifida patients aged between 0 and 16 years, who had no surgical intervention, and were performing CIC urethrally for at least 6 months. General information was recorded from electronic patient record, followed by telephonic/outpatient interview. Patients were divided into two groups: UCC or HCC. Patients in both groups had also used catheter from the other group at times. This study recorded the type/size of catheter used, its duration, complications, and their possible relation to type of catheter. Carer/patients overall satisfaction was recorded on a scale of 1–10 and their preference about the type of catheter they wish. The data were analyzed using SPSS ( P- value < 0.05 as significant). Results: One hundred one patients were included in the study: 53 UCC and 48 HCC. There was no significant difference between gender/associated conditions/age at start of CIC or duration of CIC. The mean time taken to perform the procedure was similar in both groups: UCC 9.7 min vs HCC 8.8 min. Difficulty in insertion was felt in 20, UCC 12 vs HCC 8 ( P = 0.15), recurrent UTIs UCC 12 vs HCC 17 ( P = 0.09), median patient satisfaction UCC 8/10 (3–10) and HCC 10/10 (7–10) ( P = 0.63). Request for change of catheter was made by 10 from UCC group to HCC vs none from HCC ( P ≤ 0.05).When given a choice, 28/53 (52.8%) in UCC and none (0%) in HCC group ( P ≤ 0.0001) preferred to change to the other type of catheter, mainly for convenience of use of the product. Per year per patient cost was UCC US 389 vs HCC US 2820. Discussion: Many un-modifiable factors contribute to the outcome of CIC. Despite claims of superiority by manufactures of some catheters over others, strong evidence is lacking especially in children. This study has shown no difference in the complications between UCC and HCC. Conclusion: There is no significant difference in complication rates with urethral CIC in patients using either UCC or HCC. A significant majority would prefer to use HCC mainly because of convenience of use of the product though at a seven times higher cost. Summary Table Variables Total UCC HCC P -value Difficulty in insertion 20 12 8 0.15 Recurrent UTIs 29 12 17 0.09 Want to change catheter 10 10 0 <0.05 HCC, hydrophilic-coated catheter; UCC, uncoated catheter.